Mindfulness‐based stress reduction improves irritable bowel syndrome (IBS) symptoms via specific aspects of mindfulness. Issue 9 (7th April 2020) - Naliboff, Bruce D.; Smith, Suzanne R.; Serpa, John G.; Laird, Kelsey T.; Stains, Jean; Connolly, Lynn S.; Labus, Jennifer S.; Tillisch, Kirsten
Abstract: Background: Irritable bowel syndrome (IBS) is a common and often debilitating chronic gastrointestinal disorder characterized by abdominal pain and altered bowel habits. Pharmacological treatments are often ineffective, leading to the development of a variety of behavioral interventions. Mindfulness‐based stress reduction (MBSR) is one such program that has shown efficacy in reducing gastrointestinal (GI) symptoms and improving quality of life (QOL). This single‐arm intervention study examines the association of clinical outcomes with changes in specific aspects of mindfulness. Methods: Adults with IBS (53 women, 15 men) participated in an 8‐week MBSR class. Primary outcomes of GI symptom severity, quality of life, and GI‐specific anxiety, as well as specific aspects of mindfulness using the Five Factor Mindfulness Questionnaire (FFMQ), were assessed at baseline, post‐treatment, and 6‐month follow‐up. Key Results: Gastrointestinal symptom responder rate was 71%, and there was a significant pre‐post treatment change for three of the five FFMQ scales. Regression analysis indicated that change in the Act with Awareness ( P = .02) facet of mindfulness was the strongest predictor of GI symptom and QOL improvement. Conclusions & Inferences: Mindfulness‐based stress reduction training was associated with robust improvements in GI symptoms and associated problems in participants with IBS. Although significant increases in 3 of the 5 measured facets of mindfulness were found, regression analyses suggest that increases in the ability to retain present moment focus and act with awareness may be particularly important for improving outcomes in individuals with IBS. These results may inform the refinement of mindfulness‐based protocols specifically for treatment of IBS. Abstract : MBSR led to a GI symptom responder rate of 71% and a significant pre‐post treatment change for three of five facets of mindfulness (FFMQ scales). Regression analysis indicated that change in the Act with Awareness (p = .02) facet of mindfulness was the strongest predictor of GI symptom and QOL improvement. Increases in the ability to retain present‐moment focus and act with awareness may be particularly important for improving outcomes in individuals with IBS